A meta-analysis of self-determination theory-informed intervention studies in the health domain: effects on motivation, health behavior, physical, and psychological health. Issue 2 (3rd April 2021) - Ntoumanis, Nikos; Ng, Johan Y.Y.; Prestwich, Andrew; Quested, Eleanor; Hancox, Jennie E.; Thøgersen-Ntoumani, Cecilie; Deci, Edward L.; Ryan, Richard M.; Lonsdale, Chris; Williams, Geoffrey C.
ABSTRACT: There are no literature reviews that have examined the impact of health-domain interventions, informed by self-determination theory (SDT), on SDT constructs and health indices. Our aim was to meta-analyse such interventions in the health promotion and disease management literatures. Studies were eligible if they used an experimental design, tested an intervention that was based on SDT, measured at least one SDT-based motivational construct, and at least one indicator of health behaviour, physical health, or psychological health. Seventy-three studies met these criteria and provided sufficient data for the purposes of the review. A random-effects meta-analytic model showed that SDT-based interventions produced small-to-medium changes in most SDT constructs at the end of the intervention period, and in health behaviours at the end of the intervention period and at the follow-up. Small positive changes in physical and psychological health outcomes were also observed at the end of the interventions. Increases in need support and autonomous motivation (but not controlled motivation or amotivation) were associated with positive changes in health behaviour. In conclusion, SDT-informed interventions positively affect indices of health; these effects are modest, heterogeneous, and partly due to increases in self-determined motivation and support from social agents.